Evaluation of Lemon Grass (Cymbopogon citratus) Oil as a Growth Promoter on Broiler Chicken - Tiwari, M. R.; Shah, B.; Jha, A. K. (Journal of Agriculture and Environment, 2019)
Available with full text.